Do the Einstein-matter field equations always predict the existence of light rings in black-hole spacetimes? - Shahar Hod (European Physical Journal C: Particles and Fields, 2022)
Abstract We are used to think of null circular geodesics as an integral part of black-hole spacetimes. In the present compact paper we reveal the physically interesting fact that, contrary to the general belief, the non-linearly coupled Einstein-matter field equations do not a priori guarantee the existence of external light rings in extremal black-hole spacetimes. This observation raises the intriguing possibility of having extremal black-hole spacetimes that possess no external light rings. We prove that these unique black holes, if exist, are characterized by non-positive tangential pressures on their surfaces.